Investigation into phase-resolved optical technique for latent fingerprint detection and bioimaging - Dinish Unnimadhavakurup Soudamini Amma (2008)
In this context a sensitive Phase-Resolved (PR) imaging technique is proposed to overcome the above-mentioned major limitations. A theoretical formulation of PR imaging was carried out by incorporating the homodyne and heterodyne concept of signal processing.